Consent for Intimate Exams on Unconscious Patients: Sharpening Legislative Efforts. Issue 1 (10th February 2022) - Friesen, Phoebe; Wilson, Robin Fretwell; Kim, Soyoon; Goedken, Jennifer
Abstract: The practice of nonconsensual intimate exams performed on unconscious patients by medical students during their training has received significant attention in the last several years. Clinicians, medical students, bioethicists, lawyers, and the public have called for explicit and specific consent to take place before all educational intimate examinations of unconscious patients. In response, since January of 2019, dozens of bills have been proposed in more than twenty states, and thirteen of these have been signed into law (in addition to six that passed before 2019). Here, we consider the content of these enacted bills, drawing attention to five variable features and offering these five corresponding legislative recommendations, in hopes of narrowing in on the appropriate ethical scope of consent laws surrounding educational intimate exams: (1) use gender‐neutral language; (2) include all intimate exams, not solely pelvic exams; (3) focus on unconscious patients; (4) focus on educational exams; and (5) regulate systems, not individuals .